IMPROVING MATHEMATICS LEARNING OUTCOMES THROUGH THE CONTEXTUAL TEACHING AND LEARNING MODEL ASSISTED WITH CHARACTER CALENDAR - Fira Demilia; Agung Setyawan (Citra Dharma Cindekia, 2022)
One way that can be used to make mathematics learning more concrete and easy to understand is the contextual model of media-assisted teaching and learning. Classroom Action Research has the aim of improving mathematics learning outcomes for arithmetic operations on integers, addition and subtraction in class I at SDN Bintoro 05 Jember by using the Contextual Teaching and Learning model with the help of a Character Calendar. Contextual Teaching And Learning Learning Model is a learning model that connects material with the real world. The method used is the Class Action Research method with the Kemmis and MC Taggart spiral cycle which has 2 cycle stages. The approach used in this research is descriptive quantitative. The results of the research that have been carried out show that the application of the Contextual Teaching and Learning model assisted by the Character Calendar can affect student learning outcomes with a significant increase in results in the first cycle of 50% with an average value of 70 in addition and a percentage of 50% with an average score of 62.5 on subtraction. The next increase can be seen in the second cycle of 100%.